(untitled) (Journal of Computational Mathematics, 2005)
Based on the analysis of [7] and [10], we present the mixed finite element approximation of the variational inequality resulting from the contact problem in elasticity. The convergence rate of the stress and displacement field are both improved from O(h^3/4) to quasi-optimal O(h|logh|^1/4). If stronger but reasonable regularity is available, the convergence rate can be optimal O(h).